Caracterização literária do conto angolano Nostempo de miúdo, de Boaventura Cardoso, e análise da contribuição da parataxe para o alcance do efeito de tensão na obra - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
In the present study, we analyze how the parataxis use contribute to the short story Nostempo de miúdo, by the Angolan writer Boaventura Cardoso, by achieving the tension present in that text. The aim is to overcome the apparent compartmentalization between the areas of Linguistics and Literature, as well as highlight the study of African literary texts, which are often excluded or made invisible. This is a qualitative study, more specifically a content analysis. To achieve the intended objectives, the following steps were completed: reading the short story Nostempo de miúdo; bibliographical research on the structuring elements of the story, based on Propp (2001) and D’Onofrio (2007); conceptualization of “tension”, according to Baroni (2007), Cortázar (2008) and Poe (1846); identification and classification of sentences present in the text according to Traditional Grammar and Functionalism, based on Bechara (2019) and Halliday (2014); text conceptualization, according to Halliday and Hasan (1976) and Koch (1997); and investigation of the effects achieved with the use of paratactic clauses in the short story Nostempo de miúdo, based on Bakhtin (2019) and Martins (1989). From this, it stands out: 1) that the tension that permeates the story comes from its relationship with the socio-historical context revealed by it; and 2) the fact that the linguistic choices made in the production of a literary text – as well as other texts – enable the expression of certain effects, such as tension. By highlighting these aspects, the study shows that certain effects are better elaborated depending on the syntactic constructions used by the author of the text, and that this helps the understanding of the piece of work.
Keywords: Escolhas linguísticas; Texto literário; Parataxe; Tensão; CNPQ:: LINGÜÍSTICA, LETRAS E ARTE